A comprehensive study on the effect of pilot injection, EGR rate, IMEP and biodiesel characteristics on a CRDI diesel engine. (1st March 2020) - Jaliliantabar, Farzad; Ghobadian, Barat; Carlucci, Antonio Paolo; Najafi, Gholamhassan; Mamat, Rizalman; Ficarella, Antonio; Strafella, Luciano; Santino, Angelo; De Domenico, Stefania
Abstract: Although many studies have concerned effect of different kind of biodiesel fuel on engine, there are no information about the comparison between different biodiesels in a comprehensive study and with consideration of pilot injection and EGR system. Therefore, the aim of this study is to have a comprehensive investigation of the effect of pilot injection timing and EGR system, as common ways to reduce engine emissions, on engine combustion, emissions and performance while using of different kind of the biodiesel. The brassica, cardoon, coffee, waste cooking oil biodiesels and standard diesel fuels were evaluated fuels. However, the results of the study depicted that different characteristics of the considered fuels had changed the engine response to variation of injection strategy and EGR application. The maximum reduction of combustion duration compare to diesel fuel (17.7%) was related to coffee biodiesel. Moreover, Coffee biodiesel has lowest pressure rise rate. On the other hand, cardoon had shortest ignition delay and highest combustion temperature. In addition, maximum retardation of combustion position was for brassica biodiesel fuel (19.07%). Although the N O x emission has decreased due to application of EGR (up to 86%) and pilot injection (up to 29.3%), high EGR rate in high IMEP has changed the combustion quality due to sewer changes in the combustion quality. In this condition, CO and THC emission increased severely. Higher viscosity and lower oxygen content of the coffee and cardoon biodiesel than diesel fuel decreased combustion quality and caused the higher THC, CO and soot emissions and lower N O x emissions than brassica and WCO biodiesel fuels in higher EGR rates and IMEPs. It can be stated that pilot injection and EGR are two parameters which are effective significantly on the engine characteristics and the adjusting of these parameters should be done properly specially according to the used fuel properties. Highlights: Brassica, cardoon, coffee and waste cooking oil biodiesel prepared and analyzed. Effect of pilot injection timing on the engine characteristics were investigated. Effect of EGR rate on the engine characteristics were investigated. Advanced start of pilot injection decreases the quality of the combustion. Fuel properties extremely changed the behavior of the engine.